Early childhood environmental camp in a greek port - Koresi, Georgia; Plaka, Valentina; Skanavis, Constantina (2020)
In Greece, the Port of Skyros Island has established an environmental campaign in its area, which is running for the last three years. The name of the above campaign is “SKYROS Project”. It is a cooperative project between the University of the Aegean and the Skyros Port Fund. Since 2015, every summer, academic students and researchers of the Research Center of Environmental Education and Communication of the Department of the Environment of the University of the Aegean are visiting the Island of Skyros in the spectrum of their internship requirements. The environmental communication tasks of SKYROS Project include a variety of different environmental actions. One of them is the Environmental Kids’ Camp, in which children 6 to 13 years old are participating in environmental education programs. They are being educated in a specially designed area, on how to take care, respect and protect the environment. The ultimate goal is to create environmentally active citizens with a responsible behavior. So, the main object of this research is to create a program complementary to the one already existing, based on environmental education guidelines for early childhood. For the first time, this summer of 2018, the research team of SKYROS Project will attempt to involve kids of early childhood age as well. This program provides the opportunities for young children of locals and tourists to participate in a variety of eco-social interactions, including playing and exploring the outdoors. Based on a quality assessment process, this paper will present the benefits of environmental education in early childhood in outdoors places, like a port. The extension of the environmental camp would be based on the Guidelines for Excellence of the North American Association of Environmental Education. The overall goal of these guidelines is to chart an appropriate and positive process whereby educators can start young children on their journey towards becoming an environmentally responsive youth and later on adults. Environmental education in early childhood is a holistic concept that encompasses knowledge of the natural world strengthening this way environmental literacy for all.